Diabetes Screening in the Emergency Department: Development of a Predictive Model for Elevated Hemoglobin A1c - Mary H. Smart; Janet Y. Lin; Brian T. Layden; Yuval Eisenberg; A. Simon Pickard; Lisa K. Sharp; Kirstie K. Danielson; Angela Kong (Journal of Diabetes Research)
Conclusion: In addition to age, obesity, and hyperlipidemia, a history of substance misuse was identified as an important predictor of elevated HbA1c levels among patients screened for diabetes in the ED. Our findings suggest that substance misuse may be an important factor to consider when facilitating follow-up care for patients identified with prediabetes or diabetes in the ED and warrants further investigation. Future research efforts should also include external validation in larger samples of ED patients.